2012
DOI: 10.1016/j.devcel.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Sorting by Ceramide Structure from Plasma Membrane to ER for the Cholera Toxin Receptor Ganglioside GM1

Abstract: SUMMARY The glycosphingolipid GM1 binds cholera toxin (CT) on host cells and carries it retrograde from the plasma membrane (PM) through endosomes, the trans-Golgi (TGN), and the endoplasmic reticulum (ER) to induce toxicity. To elucidate how a membrane lipid can specify trafficking in these pathways, we synthesized GM1 isoforms with alternate ceramide domains and imaged their trafficking in live cells. Only GM1 with unsaturated acyl chains sorted efficiently from PM to TGN and ER. Toxin binding, which effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
156
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(163 citation statements)
references
References 70 publications
(110 reference statements)
5
156
1
1
Order By: Relevance
“…Moreover, a retracing study of CT intoxicating retrograde pathways carried out using a subset of GM1 specified by saturated or unsaturated fluorescent-labeled ceramide chains showed that CT bound to saturated GM1, differently from the unsaturated complex forms, are directed towards late endosome compartments (that includes the MVB containing exosomes) rather than the classical Golgi/ER pathway [35]. Accordingly, it has been reported that GM1 gangliosides localize in the membrane of exosomes [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a retracing study of CT intoxicating retrograde pathways carried out using a subset of GM1 specified by saturated or unsaturated fluorescent-labeled ceramide chains showed that CT bound to saturated GM1, differently from the unsaturated complex forms, are directed towards late endosome compartments (that includes the MVB containing exosomes) rather than the classical Golgi/ER pathway [35]. Accordingly, it has been reported that GM1 gangliosides localize in the membrane of exosomes [36].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results an appealing speculation is that CTA associated with exo may derive from two distinct intracellular routes. One envisage that upon cell entry part of CT molecules may follow the long chain saturated GM1 pathway [35] presumably along with Cav-1, that leads to the CT holotoxin direct sorting to the late endosomal compartment/MVB before being secreted. The other, namely CTA1, is originated from the canonical ER retrograde pathway where, by the action of HSP90 and PDI, is translocated to the cytosol and taken up during exo formation by intraluminal vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…For CT, this requires binding of its B subunit to the ganglioside receptor GM1, which acts as the vehicle for retrograde trafficking into the TGN and ER (1).…”
Section: Cholera Toxin (Ct)mentioning
confidence: 99%
“…However, this may relate to the presence of the ceramide moiety, which was absent from our a-GM1, rather than the GM1 glycan itself. Via this ceramide, GM1 and gangliosides generally would be expected to insert into the cellular plasma membrane under the experimental conditions used (43,73,74). This cellular GM1 incorporation might indirectly influence RRV recognition of its cellular receptors and/or reduce RRV cell entry by altering membrane lipid microdomains (lipid rafts), as GM1 partitions with lipid rafts.…”
Section: Discussionmentioning
confidence: 99%